SEISMIC TOMOGRAPHY WITH P AND S DATA REVEALS LATERAL VARIATIONS IN THE RIGIDITY OF DEEP SLABS - Widiyantoro S.; Kennett B.L.N.; van der Hilst R.D. (My University, 1999)
Regional seismic tomography of the northwest Pacific island arcs using P- and S-wave arrival time data with similar path coverage reveals an oceanic lithospheric slab deflected in the mantle transition zone beneath the Izu Bonin region in good agreement with the results of earlier tomographic and other seismic studies in the region. The S-wave images, however, do not show clearly the deflection of the slab. This implies that the stagnant lithospheric slab in the transition zone is more likely a bulk-sound structure, which is strongly supported by our results from joint inversions for bulk-sound and shear wavespeeds. For the Izu Bonin region, where trench migration has been reported, the properties of the deflected slab lying on top of the 660 km discontinuity show strong bulk-sound and weak shear signatures in contrast to the descending slab itself. There is an indication in the shear images that a component of the former oceanic lithosphere is penetrating into the top of the lower mantle, suggesting that a slab split has occurred.
Keywords: RIGIDITY; SLABS; TOMOGRAPHY; P-WAVES; S-WAVES